If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying T + -16 = -23 Reorder the terms: -16 + T = -23 Solving -16 + T = -23 Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + T = -23 + 16 Combine like terms: -16 + 16 = 0 0 + T = -23 + 16 T = -23 + 16 Combine like terms: -23 + 16 = -7 T = -7 Simplifying T = -7
| 4+5t-3=8t+3-2t | | 4/4=48/4 | | 4a-5a= | | 0.5(m-2)=5 | | x/9=29=41 | | n/7=-42 | | -b/6-7=-11 | | 8x^2-70x+17= | | 3(1/10)s=6(1/5) | | 14/3-2 | | cos3.14/4 | | g(n)=n^2+4 | | 3a+-2a=-17 | | 1=-4/3(-4) | | 10=-5/6× | | 12x+36=7x | | 1-3(-1+2v)-3v= | | cx-d=0solvex | | 8/t;t=4 | | 12(2x^2-11x-40)=0 | | X^8+16=0 | | -(7/8)k=-21 | | -4(9s+8)+7s=26 | | (11x-47)=(6x-2) | | 12x-8x^3=0 | | -32x+-20+9= | | 20c^2+17c-63= | | B+0.015t=0.022N | | 6x-9+5+8=-98 | | 2r^2+11r+14= | | a-6=4-(9+a) | | -3+4y=9 |